PELATIHAN WIRAUSAHA DAN KEMANDIRIAN FINANSIAL PADA PONDOK PESANTREN YATIM DHUAFA AL-FIRDAUS KEMILING PERMAI BANDAR LAMPUNG - Ruslaini Ruslaini; Abizar Abizar; Nina Ramadhani (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2021)
Al-firdaus Islamic boarding school is located in the Kemiling Permai Village, Kemiling Bandar Lampung District. This boarding school has students from various levels of education, starting from elementary, junior high and senior high school. This pesantren has a unique geographic location, which is located on the outskirts of the Bukit Kemiling Permai housing complex. Pesantren Al-firdaus want to form cottage business units and the independence of students in entrepreneurship so that they do not depend only on donors and the government. At the level of entrepreneurship fostering and financial independence of pondok still not well managed, some of the potential that can be developed for the establishment of cottage business charities is still not optimally exploited so it requires assistance. The method of community service activities carried out is to explore problems, an urgent problem was found, namely the lack of entrepreneurial skills and poor marketing techniques as well as financial management, so that entrepreneurial training, assistance in management aspects and marketing technology were carried out. The result of this activity was an increase in entrepreneurial skills, financial management and good marketing for students and administrators, promising the independence of the cottage